TEACHING STUDENTS' LISTENING SKILL THROUGH DICTOGLOSS TECHNIQUE - Windy Widiasmara, - (2012)
This study aims to investigate the use of dictogloss technique in teaching students' listening skill. The study used a quasi experimental design with two classes of eleventh graders at one of the public senior high schools in Cianjur as the sample. The data were obtained through a pre-test, post-test, questionnaire, and interview. The data gathered through pre-test and post-test were computed one by one using SPSS Statistics 17 for Windows, data from questionnaire were analyzed based on the frequency of students' answers and then were calculated and interpreted into percentage, while data from interview were transcribed and interpreted. The result of the study showed that the technique was effective in elevating students' listening scores. The statistical computation showed that dictogloss technique was likely to be effective in teaching students' listening skill (tobt2.158>tcrit2.021, r= 0.494). The data from the questionnaire showed that dictogloss technique was positively responded by the students. Moreover, the data from interview confirmed that students experienced many benefits from the technique. Based on these findings, it is recommended that dictogloss technique be applied in teaching listening. The technique gives many advantages and offers a challenging and interesting learning experience.